Room-temperature lasing in colloidal nanoplatelets via Mie-resonant bound states in the continuum - Wu, Mengfei (2020)
Solid-state room-temperature lasing with tunability in a wide range of wavelengths is desirable for many applications. To achieve this, besides an efficient gain material with a tunable emission wavelength, a high quality-factor optical cavity is essential. Here, we combine a film of colloidal CdSe/CdZnS core-shell nanoplatelets with square arrays of nanocylinders made of titanium dioxide to achieve optically pumped lasing at visible wavelengths and room temperature. The all-dielectric arrays support bound states in the continuum (BICs), which result from lattice-mediated Mie resonances and boast infinite quality factors in theory. In particular, we demonstrate lasing from a BIC that originates from out-of-plane magnetic dipoles oscillating in phase. By adjusting the diameter of the cylinders, we tune the lasing wavelength across the gain bandwidth of the nanoplatelets. The spectral tunability of both the cavity resonance and nanoplatelet gain, together with efficient light confinement in BICs, promises low-threshold lasing with wide selectivity in wavelengths.